Exit Strategy for Treatment of Neovascular Age-Related Macular Degeneration in a Real-World Setting: Wishful Thinking? - Eastline, Michael; Said, Sadiq; Bosch, Martina Monika; Knecht-Bosch, Pascal (Klinische Monatsblätter für Augenheilkunde, 2025)
Introduction To analyze our outcome for patients with neovascular age-related macular degeneration (nAMD) treated with aflibercept in a treat-and-extend regimen pursuing an exit strategy (with best possible adherence to the “Bern” exit criteria) over 6 years in a real-world setting. The primary objective of the study was to investigate the proportion of patients who were able to achieve and maintain treatment exit.Methods This is a retrospective chart review study of treatment-naïve patients diagnosed with nAMD receiving intravitreal aflibercept injections performed at our department with at least 2 years of follow-up visits. The primary outcome was the percentage of patients able to achieve and maintain the treatment exit regarding intravitreal anti-VEGF injections. Further outcome measures were best-corrected visual acuity (BCVA), incidence of recurrence after treatment cessation, duration of therapy, and number and intervals of injections.Results There were 31 eyes of 25 patients included in this retrospective study. The observation period was from September 1, 2017 to August 31, 2023. Of all included patient eyes, 22.6% (n = 7) reached exit criteria. Of all the “exit” patients, 28.6% (n = 2) suffered from disease relapse and therapy was restarted at a mean (± SD) of 41.5 ± 12.5 weeks (range: 29 to 54 weeks). Regarding the eyes that met treatment exit, 5 of 31 (16.1%) had no disease recurrence in the observed study period. The median BCVA (Snellen decimal; ± interquartile range: IQR) changed from 0.63 (0.27) at baseline to 0.63 (0.4) in the first year, 0.63 (0.3) in the second year, 0.63 (0.46) in the third year, 0.63 (0.3) in the fourth year, 0.63 (0.4) in the fifth year, and 0.4 (0.04) in the sixth year. The median number of injections (± IQR) per eye in the first year of treatment was 8 (2), in the second year 5 (2), in the third year 5 (2.5), in the fourth year 5 (1), in the fifth year 3 (0.8), and in the sixth year 3 (0). Extension of the treatment interval after the loading phase in weeks was achieved up to a median (± IQR) of 5.8 (4) in the first year, 8.4 (6) in the second year, 8 (5.7) in the third year, 9.4 (5.6) in the fourth year, 7 (6.9) in the fifth year, and 8.4 (3.1) in the sixth year of observation.Discussion Our study indicates a lower rate of patients reaching exit criteria with a treat-and-extend regimen compared to clinical study settings, and a similar recurrence rate of nAMD after treatment cessation. Nonadherence to a strict treat-and-extend protocol might influence the result.
Keywords: neovascular age-related macular degeneration; anti-VEGF; treat-and-extend; exit-strategy; aflibercept